Red zone blues: Violence and nostalgia in Guatemala City. (September 2019) - Saunders-Hastings, Katherine
Based on ethnographic research in a Guatemala City mara territory, this article examines the place of nostalgia in residents' accounts of spiralling insecurity and gang violence. Anchoring many depictions of their circumstances past and present, emotional and narrative structures of decline and nostalgia pervaded interviews, interactions, and the research experience here. While discourses of loss and longing pose certain methodological quandaries for attempts to reconstruct processes of change in a volatile environment, I propose that they do communicate true and valuable information for understanding the social experience of violence in Guatemala City's gang territories. I also argue for understanding nostalgia as a resource – for inhabitants and for ethnographers alike – in the face of 'ontological insecurity' in violent fields. Providing reassuring narratives and tools for articulating normative claims for our informants, nostalgia also holds a strong appeal for ethnographers, presenting both dilemmas and possibilities in researching and representing contemporary insecurity.